Human Resource Development in Islamic Higher Education through Religious Moderation Values: Fostering Civil Society - Hanif, Hanif; Mukri, Moh; Madnasir, Madnasir; Siatan, Mairizal S. (Ulumuna, 2024)
The mission of Islamic Higher Education Institutions (IHEIs) is to advance Islam as a mercy to all creation (raḥmah li al-‘ālamīn). A manifestation of Islam, raḥmah li al-‘ālamīn, is the practice of religious moderation in campus life and society, characterized by the adoption of pillars such as national commitment, anti-violence, tolerance, and adaptation to local culture. This study seeks to compare human resource development (HRD) methods by enhancing the values of religious moderation in three IHEIs. A comparative descriptive qualitative method was used to understand the HRD of three IHEIs that were the objects of research to identify similarities and differences. The study found that all three IHEIs used a similar approach, such as focus group discussions, training, and webinars. These efforts have only reached the internalization stage in strengthening the understanding of religious moderation. The study's results recommend an HRD framework that integrates religious moderation into the organizational culture to encourage the realization of a civil (Madani) society.